PROFESIONALISME AUDITOR DAN TINGKAT MATREALITAS DALAM MENENTUKAN KETEPATAN PEMBERIAN OPINI PADA KANTOR AKUNTAN PUBLIK (KAP) DI BANDUNG - Sakti Muda Nasution (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2016)
ABSTRACT : The growth of business world in Indonesia time to time felt progressively competitive. Every company has an effort to survived in business competition. Company management need the service of third party to have the financial statement accountable to outside party and can improve the management company credibility, such as auditor external. Target of this Research is to know the applying of professionalism of auditors and materiality level at Public Accountant in Bandung, and to know the influence of professionalism of auditors and materiality level to accuracy of opinion at Public Accountant firms in Bandung simultaneously and partially.In SPAP SA Seksi 200 PSA No. 04 ( 2001) expressing that " In executing audit to come to at one particular opinion statement, auditor have to act as the expert in the professional of accountancy and auditing area". Others in SPAP (SA Seksi 312, PSA No. 29) is also said that "Opinion statement for certain element in storey of financial level materiality statement (do not full of opinion), that my not be expressed by if auditors express don’t pass an opinion or he also express factious opinion for storey level of materiality of financial statement as a whole, because opinion statement don’t full of in this case tend to will blur meaning don’t of statement opinion and the factious opinion to the storey level of materiality of financial statement as a whole".